PELAKSANAAN PRAKTIK SEWA POHON MANGGA DITINJAU DARI HUKUM ISLAM: Studi Kasus Desa Sukorejo Kecamatan Sumber Rembang - Sodikin; Irvan Iswandi (Jurnal Penelitian Multidisiplin Ilmu, 2022)
This research began with the implementation of the practice of renting mango trees in Sukorejo Village, Sumber District, Rembang Regency. In this village, many people use mango trees by renting them out. This transaction makes the mango fruit as a benefit. The payment for renting mango trees in Sukorejo Village uses a prepayment system that does not take into account the harvest once or twice a year and even fruit or no fruit. The formulation of the problem taken from the background above is how to implement the practice of renting mango trees in Sukorejo Village, Sumber District, Rembang Regency and how to review Islamic law on the system in mango tree rental in Sukorejo Village, Sumber District, Rembang Regency. According to the type of research included in this field research is included in the qualitative approach. The study chose the implementation of the mango tree rental practice that occurred among the people of Sukorejo Village, Sumber District, Rembang Regency. The data obtained will be processed and analyzed with ijarah theory to answer the formulation of the problem. From this research, it can be concluded that the mango tree rental contract in Sukorejo Village, Sumber Subdistrict, Rembang Regency is not in accordance with the ijarah principle because one of the pillars and conditions in ijarah is not fulfilled, namely in terms of benefits, where the benefits of the mango tree are mangoes and mangoes are part of the benefits. from the mango tree itself, while in the principle of ijarah, Jumhur scholars forbid renting out trees for fruit because it is unclear whether the tree bears fruit or not (gharar). The payment system for renting mango trees in Sukorejo Village is in accordance with the ijarah principle, because the payment system is carried out, namely, after an agreement on the rental price occurs, the tenant will hand over cash. And for a review of Islamic law on the expiration of the contract in the lease of mango trees in Sukorejo Village, it is in accordance with the ijarah principle because it is clear that in the expiration of the contract, the principle of ijarah rental period must be clear, namely the minimum or maximum time for leasing goods or services.